Radiologic and Pathologic Findings of Axillary Intraductal Papilloma Arising in Accessory Breast Tissue: A Case Report and Literature Review - Bae, Seong Jae; Eun Yang, Go (Current Medical Imaging, 2022)
Introduction: This is a rare case report of axillary intraductal papilloma arising in accessory breast tissue. Case Presentation: A 49-year-old woman presented to our clinic with a palpable right axillary mass that had first appeared 6 months earlier. Mammography and ultrasonography of the right axilla revealed an ovoid mass surrounding accessory breast tissue. Ultrasound-guided 14-G core-needle biopsy was performed and pathologically revealed intraductal papilloma without atypia. Conclusion: Since ectopic breast tissue is affected by the same pathologic processes as normal breast tissue, a core-needle biopsy can be used to identify the suspicious lesions in axillary breast tissue.
Keywords: mammography